2011
DOI: 10.3389/fphar.2011.00081
|View full text |Cite
|
Sign up to set email alerts
|

Voltage- and Temperature-Dependent Allosteric Modulation of α7 Nicotinic Receptors by PNU120596

Abstract: Alpha7 nicotinic acetylcholine receptors (α7 nAChR) are widely distributed throughout the central nervous system and are found at particularly high levels in the hippocampus and cortex. Several lines of evidence indicate that pharmacological enhancement of α7 nAChRs function could be a potential therapeutic route to alleviate disease-related cognitive deficits. A recent pharmacological approach adopted to increase α7 nAChR activity has been to identify selective positive allosteric modulators (PAMs). α7 nAChR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…At 37°C PNU-120596-potentiated responses were only 12 Ϯ 3% (88% reduction) of the baseline responses obtained initially at 23.5°C but recovered when the temperature was returned to 23.5°C. This result is consistent with recent findings (Sitzia et al, 2011) and predicts that there may be temperature dependence of the PNU-120596 cytotoxicity. However, because recent studies of the concentration dependence of PNU-120596 potentiation (Williams et al, 2011b) suggested that potentiation may be reduced with high concentrations of the agent owing to the induction of resistant forms of desensitization, producing an inverted U concentration-response relationship, we also wished to test whether temperature might have the effect of shifting this concentration-response relationship so that potentiation by a lower concentration of PNU-120596 might show less temperature sensitivity.…”
Section: Concentration Dependence Of Ach-evoked Peak Current and Net supporting
confidence: 93%
See 3 more Smart Citations
“…At 37°C PNU-120596-potentiated responses were only 12 Ϯ 3% (88% reduction) of the baseline responses obtained initially at 23.5°C but recovered when the temperature was returned to 23.5°C. This result is consistent with recent findings (Sitzia et al, 2011) and predicts that there may be temperature dependence of the PNU-120596 cytotoxicity. However, because recent studies of the concentration dependence of PNU-120596 potentiation (Williams et al, 2011b) suggested that potentiation may be reduced with high concentrations of the agent owing to the induction of resistant forms of desensitization, producing an inverted U concentration-response relationship, we also wished to test whether temperature might have the effect of shifting this concentration-response relationship so that potentiation by a lower concentration of PNU-120596 might show less temperature sensitivity.…”
Section: Concentration Dependence Of Ach-evoked Peak Current and Net supporting
confidence: 93%
“…Although PNU-120596 and TQS appear to bind at similar sites in the intrasubunit cavity formed by the four membrane-spanning helices (Young et al, 2008;Gill et al, 2011), there may be alternate protein-PAM interactions, with increased differences in the response to membrane fluidity changes that occur at higher temperature. Although increased temperature had only a modest effect on receptor activation by the allosteric agonist 4-(4-bromophenyl)-3a,4,5,9b-tetrahydro-3H-cyclopenta[c]quinoline-8-sulfonamide (Jindrichova et al, 2012), Sitzia et al, 2011 reported that the potentiating activity of SB-206553, a PAM with properties intermediate to those of the type I and type II PAM classes (Dunlop et al, 2009), was also reduced at 37°C. Although the published data agree that type I PAMs appear to lack in vitro cytotoxicity (at the concentrations of agonists and modulators tested), the data are contradictory regarding the in vitro toxicity of the type II PAM PNU-120596 (Ng et al, 2007;Hu et al, 2009;Dinklo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting this possibility of choline, PNU-120596 was recently reported to enhance the effects of subthreshold, physiologic concentrations of choline on native a7 nAChR in hypothalamic neurons . Although the enhancement seen using in vitro a7 nAChRs preparations is greatly decreased when experimental temperatures increase to near physiologic levels (Sitzia et al, 2011;Williams et al, 2012), apparently it is not completely eliminated given that PNU-120596 required enhanced endogenous a7 nicotinic activation to produce the antinociceptive effects in our tests. In addition, Williams et al, (2012) showed that, although the effects of PNU-120596 are strongly temperature dependent, physiologic factors, such as serum albumens, reverse this temperature dependency.…”
Section: Discussionmentioning
confidence: 84%